A Study of School Lunch Food Choice and Consumption among Elementary School Students - Johnson, Ping Hu; Gerson, Deanne; Porter, Kandice; Petrillo, Jane (International Journal of Child Health and Nutrition, 2015)
Background: School lunches that are part of the National School Lunch Program must meet specific nutrition requirements. It is unknown whether students eat school lunches in a balanced manner. This study examined which lunch food items children eat/toss, and consumption differences between sexes, and between students at a Non-Title 1 school where most students purchase school lunches and a Title 1 school where most students receive free or reduced-priced lunches. Methods: Students in both schools were observed unobtrusively for five consecutive days. Trained observers recorded the discarded food items on a checklist listing the menu items for the day. The final analyses (t- tests, z tests) included data from 2,826 student-meals. Results: Entrees similar to those offered in fast food restaurants (i.e., chicken nuggets, pizza, nachos, corndogs) were favored by most students. Fresh fruits and vegetables were not selected or consumed frequently. Boys consumed more food in the fast food, starches, and dessert categories, while girls consumed more soup, salads, and vegetables. Title 1 school students consumed more food in all categories except bread, pasta, and sandwiches than Non-Title 1 school students. Conclusions: Students’ preference of unhealthy lunch items may decrease the health benefits that school lunches attempt to provide.